(untitled) (Nigerian Journal of Technology, 2017)
Several researchers have studied the water quality of the upper and lower stretches of River Kaduna with little on the middle stretch of the river. Besides, no work has ever been done on mapping the water quality of the said river. Hence, the middle stretch of River Kaduna was monitored for 12 months starting from June, 2016 to May, 2017, covering both rainy and dry seasons in 15 sampling locations to generate data for water quality mapping. However, eight water quality parameters were analyzed namely; temperature, turbidity, pH, dissolved oxygen, biochemical oxygen demand (BOD), chemical oxygen demand (COD), total nitrogen and total phosphorus using standard methods. Rainy season results were separated from dry season results and were used in mapping the water quality of the river for both seasons using ArcGIS 10.5. It was concluded that the water temperature of the river was within the permissible limit set by U.S. EPA during both seasons while the other water quality parameters apart from turbidity and pH deteriorated more during dry season. In addition, COD and total phosphorus were found to be the only parameters that never met the requirement set by U.S. EPA throughout the sampling period irrespective of the sampling location and season. This is because the least measured concentrations of COD and total phosphorus were 35.34 mg/l and 0.109 mg/l, respectively. It was recommended that farming activities at the river banks should be banned as the fertilizers used by farmers easily drain into the river and increase the phosphorus and COD concentrations. http://dx.doi.org/10.4314/njt.v37i1.33